Answer:
3(x−1)=18
Answer:
x=7
Step-by-step explanation:
\frac{3\left(x-1\right)}{3}=\frac{18}{3}
x-1=6
x-1+1=6+1
x=7
Hope I helped
brainliest plz
1. Given
2. Combine like terms
3. Subtraction POE (Property of Equality)
Answer:
NO
Step-by-step explanation:
- Try to replace x by -50
- y= 390 + 11*(-50) = -160
- in the table we have -210 so the table doesn't represent the equation
To do this, multiply 3/4 by 1/2 and you end up with 3/8 lb. or 0.375 lb.
Hi there!!!
So using this rule:
Area = base * height
20ft * 15ft = 300ft^2
↑ ↑
base height
HOPE IT HELPS U!!!!!!!!!
THE ANSWER IS 300 FT^2
~ TRUE BOSS